The impact of the EU ETS on the sectoral innovation system for power generation technologies: findings for Germany - Karoline S. Rogge; Volker H. Hoffmann (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2009)
This paper provides an overview of early changes in the sectoral innovation system for power generation technologies which have been triggered by the European Emission Trading Scheme (EU ETS). Based on a broad definition of the sector, our research analyses the impact of the EU ETS on the four building blocks knowledge and technologies, actors and networks, institutions and demand by combining two streams of literature, namely systems of innovation and environmental economics. Our analysis is based on 42 exploratory inter-views with German and European experts in the field of the EU ETS, the power sector and technological innovation. We find that the EU ETS mainly affects the rate and direction of the technological change of power generation technologies within the large-scale, coal-based power generation technological regime to which carbon capture technologies are added as a new technological trajectory. While this impact can be interpreted as defensive behaviour of incumbents, the observed changes should not be underestimated. We argue that the EU ETS' impact on corporate CO2 culture and routines may prepare the ground for the transition to a low carbon sectoral innovation system for power generation tech-nologies.
urn:nbn:de:0011-n-1180740
Keywords: 330; EU emission trading scheme (EU ETS); innovation system; power sector; Emissionshandel; EU-Umweltrecht; Innovation; Elektrizitätswirtschaft; Deutschland